Addressing environmental challenges in supply chains: A multi-method approach - Arbabiun, Pouneh (2024)
The climate breakdown requires us to profoundly rethink our relationship with the natural environment and our production and consumption systems. Over the last 40 years, much attention has been paid to the question of how to best organise supply chains in order to embed environmental practices and deliver positive environmental outcomes. Research in the field of green supply chain management has shed light on different facets of this question, with specific contributions mobilising empirical and modelling methods, but rarely has it brought these approaches under the same roof to broaden the conversation. At the same time, a number of scholars have called for engagement with ecological perspectives and concepts within supply chain management as a way to explore how to advance towards ‘strong’ or ‘true’ sustainability as opposed to instrumental approaches. These constitute the fundamental challenges and broader context that motivated the ideas in this thesis. In an attempt to offer a multi-method approach and ecologically focused contribution to supply chain management, the research presented here comprises three distinct but complementary studies that mobilise different methodologies – modelling, systematic literature review, Delphi – and concepts – carbon footprint reduction, planetary boundaries, ecological approaches. The thesis is structured around three independent research papers that present these studies. The first paper focuses on the economic incentives of firms in a two-echelon supply chain, consisting of a manufacturer and a retailer, to invest in their emission reduction efforts. It proposes a cost-sharing mechanism for collaboration in the supply chain, where the retailer supports the manufacturer in its efforts to reduce emissions. The problem is modelled as a retailer-led Stackelberg game in which optimal pricing and emission reduction decisions are obtained, and the effectiveness of the cost-sharing mechanism is investigated. Having conducted a game modelling with the purpose of emissions reduction in a two-echelon supply chain, the second research paper focuses on environmental degradation from a wider perspective and at the macro (global) level. Therefore, this paper assesses the engagement level of the sustainable supply chain management literature with the concept of planetary boundaries (PBs). In fact, the PBs framework has been considered here as an analytical lens to evaluate the supply chain management literature contribution to ecological restoration. A systematic review was developed to identify and analyse relevant supply chain management publications between 2008 and 2021. Having conducted a literature review on the interconnection between the supply chain management literature and PBs, the third research paper further explores some of the ideas and research avenues identified through iterative consultation with sustainable supply chain management researchers. A Delphi study has been developed to identify how the field of supply chain management may move towards more ecological approaches. Overall, this thesis aims to explore the shift in sustainable supply chain management towards more ecological approaches. The collective insights from the three studies shed light on the value of different methods and concepts and on promising research avenues to drive positive environmental impact in supply chains.